ECOLOGICAL INITIATIVES OF BUSINESS AS A FACTOR FOR GROWTH OF ITS COMPETITIVENESS - Пиртко, С. (SWorldJournal, 2025)
The article examines the current state of influence of environmental responsibility of business on ensuring its competitiveness. The key characteristics of environmentally responsible business are identified: voluntariness and proactivity, integration int